The implications of Nel Noddings’ ethics of care for fostering teacher-student relationships in higher education - Chen, Ming-Kuo; Shih, Yi-Huang (Frontiers in Education, 2025)
Nel Noddings’ ethics of care offers a sophisticated and comprehensive theoretical framework for critically reimagining the teacher-student relationship within the context of higher education. This paradigm stands in stark contrast to traditional pedagogical approaches that predominantly emphasize cognitive outcomes, often at the expense of emotional and social development. By incorporating Noddings’ ethics of care into the dynamics of teacher-student interaction, higher education institutions have the potential to foster a more supportive and nurturing learning environment—one that not only facilitates intellectual growth but also nurtures students’ emotional well-being, sense of social responsibility, and a deeper sense of belonging. Noddings’ conceptualization of care invites us to reconceptualize the teacher-student relationship, recognizing it as not solely a transactional exchange of knowledge, but as a relational practice rooted in emotional and ethical care. Consequently, higher education must recalibrate its focus to emphasize the integration of personal values with social responsibility. By cultivating a culture grounded in care and dialogue, higher education can facilitate the holistic development of students, equipping them with the empathy and social consciousness needed to become responsible global citizens. This approach is closely aligned with the humanistic principles underpinning broader educational objectives. This paper seeks to examine the application of Noddings’ ethics of care in higher education, investigating its potential to enrich and transform the teacher-student relationship.